Perbandingan Teori 4 Dimensi Keagamaan (4BDRS) dan Teori Tahapan Iman Fowler untuk Riset Psikologi Agama di Indonesia: Perbedaan, Perkembangan Terkini dan Implikasi - Lindawati Lindawati; Ihan Martoyo (Konsorsium Psikologi Ilmiah Nusantara, 2022)
A lot of studies in psychology of religion have been conducted in Indonesia, however not many used tested theoretical frameworks. In this short review, two theories that are growing in international research and received considerable attention in psychology of religion studies in Indonesia, will be surveyed and compared. The 4 Basic Dimensions of Religiousness Scale (Saroglou) provides a multidimensional approach to religiousness that involves the aspects of: (1) Cognitive (Believing), (2) Affective (Bonding), (3) Behavior, and (4) Community (Belonging). On the other side, Fowler’s Stages of Faith offers a framework to discuss the psychological structure that becomes the vessel for religious manifestation at a certain faith stage apart from the content of a specific faith. This survey and comparison will help provide options for more systematic research on psychology of religion with a more tested theoretical framework in Indonesia.